HUBUNGAN PENGETAHUAN PERAWAT RUANG RAWAT INAP TENTANG PENGGUNAAN APAR (ALAT PEMADAM API RINGAN) DENGAN TERJADINYA RESIKO BENCANA KEBAKARAN DI RUMAH SAKIT UMUM SEMBIRING DELITUA - Evfy Septriani Ginting; Ripai Siregar; Muhraza Siddiiq; Pitto Pratiwi Malau; Ana Apriana (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2023)
The hospital is one of the high-rise buildings that have the potential for fires originating from electricity, stoves, and storing flammable materials for example fuel and medical gas and installation of power plants such as generator sets which are the source of fires. Fire is an unwanted and uncontrollable occurrence of fire. The purpose of this study was to examine the relationship between knowledge of inpatient nurses regarding the use of fire extinguishers with the occurrence of fire disaster risk at Sembiring Delitua General Hospital.The design of this study used an observational analytic method through a cross sectional approach. The study population were 158 people, with sample of 61 nurses used the proportional stratified random sampling method. The research instrument was questionnaire. Data Relationship between Inpatient Nurse Knowledge about the Use of Fire Extinguishers and the Occurrence of Fire Disaster Risk in the Post-Covid-19 Pandemic at Sembiring Delitua Hospital.analysis methods were univariate and bivariate with chi square test. The results showed that from 61 nurses, 47 people (77%) had poor knowledge about the use of fire extinguishers and resulted in a high risk of fire disaster and 14 people (23%) have good knowledge about the use of fire extinguishers and with a low risk of fire disasters. The results of the univariate analysis showed that there was a significant relationship between nurses' knowledge of the use of fire extinguishers and the occurrence of fire disaster at Sembiring General Hospital with p = 0.003 < 0.05. Conclusion: nurses' knowledge about the use of fire extinguishers has a relationship with the occurrence of fire disaster risk with 4,170 times greater chance. Suggestion: the management provides training and simulations to health workers such as nurses on how to use fire extinguishers and fire emergency response.